Why Does Book Building Drive Out Auction Methods of IPO Issuance? Evidence from Japan - Kutsuna, Kenji; Smith, Richard (Review of Financial Studies, 2004)
We examine Japan's 1997 introduction of book building as an alternative to a previously required hybrid auction method. Despite higher cost for some issuers, all issuers in Japan now select book building. Book building enables more accurate valuation of firms, but gains from accurate valuation are partly redistributive. Thus book building can drive auction-method offerings from the market even if it yields no aggregate benefit. Compared to the auction regime, book building reduces issue costs for large issuers. Auctioning is less costly for small issuers, but appears to foreclose some small firms from issuing. The aggregate costs of book building and auctioning are similar. Copyright 2004, Oxford University Press.